(untitled) (Bangladesh Journal of Nuclear Medicine, 2022)
Objective: The aim of the study was to investigate thyroid function of newborn babies of mothers with differentiated thyroid carcinoma (DTC) after receiving radioactive iodine (131I) therapy (RAIT). Materials and methods: During the period of 2009 to 2014, a total of 1620 women had been treated with 131I in the thyroid division of National Institute of Nuclear Medicine & Allied Sciences (NINMAS). Patients were followed up at regular intervals systematically and were allowed to conceive with confirmation of disease free condition. A retrospective review of the medical records was done in this study. Out of 1620 patients, 1370 (84.6%) were in the reproductive age group (18-44 years). Among 1370 patients, 111 patients became pregnant after 2 years of the RAIT. Age at pregnancy ranged between 20 to 32 years (24.8 ± 4.8). All pregnant mothers were disease free and well supplemented by levothyroxine and maintained their Thyroid Stimulating Hormone (TSH) at a low normal range (0.1-1.0 mIU/L). Average serum thyroglobulin (Tg) level were below <0.02 ng/dl. Would be mothers were requested to estimate TSH of the newborns by 7 to 15 days after birth and report to us. They immediately reported the TSH test results of the babies. Results: One hundred fourteen mothers with DTC had received RAIT and conceived at a mean age of 24.8± 4.8 years (19-38 years). Out of 114 patients, 110 (96.5%) patients were papillary thyroid cancer (PTC) and 4 (3.5%) was follicular thyroid cancer (FTC). Patients were treated by 30-100 mci. The outcome of 111 pregnancies after RAIT was 108 (97.30%) delivered the healthy euthyroid babies and 3 (2.70%) had miscarriages. TSH range from 0.52 -16 mIU/L (3.69 ± 3.19) Conclusion: This study showed that RAIT in young women did not have any deleterious effects on subsequent pregnancies. All babies born by mothers with DTC after radioiodine treatment showed normal thyroid function evaluated by TSH. Bangladesh J. Nuclear Med. 25(2): 88-92, 2022